"Judge Lynch" in the Court of Public Opinion: Publicity and the De-legitimation of Lynching. Issue 2 (15th February 2019) - WEAVER, MICHAEL
Abstract : How does violence become publicly unacceptable? I address this question in the context of lynching in the United States. Between 1880 and the 1930s, public discourse about lynching moved from open or tacit endorsement to widespread condemnation. I argue this occurred because of increasing publicity for lynchings. While locals justified nearby lynchings, publicity exposed lynching to distant, un-supportive audiences and allowed African Americans to safely articulate counternarratives and condemnations. I test this argument using data on lynchings, rail networks, and newspaper coverage of lynchings in millions of issues across thousands of newspapers. I find that lynchings in counties with greater access to publicity (via rail networks) saw more and geographically dispersed coverage, that distant coverage was more critical, and that increased risk of media exposure may have reduced the incidence of lynching. I discuss how publicity could be a mechanism for strengthening or weakening justifications of violence in other contexts.